2014
DOI: 10.1587/elex.11.20140810
|View full text |Cite
|
Sign up to set email alerts
|

Multi-string AC-powered LED driver with current regulation reduction based on simple circuitry

Abstract: In this letter, a new simple circuitry LED driver with current reduction is proposed, realized and experimentally validated. The proposed circuit comprises with very few components intended for making a costeffective and compact design while still shows a high performance. The circuit reduces non-conducting time of LEDs to enhance power factor (PF) and total harmonic distortion (THD). The flicker can also be relatively reduced. By using current limiter cells, lighting variation is eliminated with respect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Secondly, the power (in Watts) of the works can be customized in the design process without changing the performance of the circuits. For instance, to increase the power in this work, either the dimming voltage can be Table I, the proposed design can gain a very high PF and a low THD as compared with the non-dimmable designs in [1,2,3]. In comparison with the dimmable AC LED driver reported in [4], the proposed design owns the similar performance with a more simple circuit structure.…”
Section: Simulation Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Secondly, the power (in Watts) of the works can be customized in the design process without changing the performance of the circuits. For instance, to increase the power in this work, either the dimming voltage can be Table I, the proposed design can gain a very high PF and a low THD as compared with the non-dimmable designs in [1,2,3]. In comparison with the dimmable AC LED driver reported in [4], the proposed design owns the similar performance with a more simple circuit structure.…”
Section: Simulation Resultsmentioning
confidence: 83%
“…Recently, various non-isolated AC-powered LED drivers with multiple LED strings have been introduced, enabling a high power factor (PF), a low total harmonic distortion (THD) as well as lows crest factor [1,2,3]. However, the dimming function which is important for a light source that the luminance can be adjusted is not available on these AC LED drivers.…”
Section: Introductionmentioning
confidence: 99%
“…The LCRs are turned on in a sequence and this process repeats in the next cycles. Additionally, it is noticeable that the power processing core owns a self-adaptive mechanism; hence, there is no need of any additional controller as in the designs reported in [4,5]. Furthermore, since only one LCR turns on at a certain period, the loss power is minimized in order to increase the power efficiency.…”
Section: A System Design and Fundamental Operationmentioning
confidence: 99%
“…Recently, there have been studies of high PF, low THD AC-directly-powered LED drivers reported in the literature [4]- [6]. Although these AC LED drivers can achieve a very high performance, they also have several shortcomings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation